2017
DOI: 10.1007/s10753-017-0681-7
|View full text |Cite
|
Sign up to set email alerts
|

CD80 Regulates Th17 Cell Differentiation in Coxsackie Virus B3-Induced Acute Myocarditis

Abstract: The cluster of differentiation protein complex, CD80/CD86, regulates Th1/Th2 differentiation in autoimmune disease. In order to establish the effects of CD80/CD86 on Th17 cell differentiation in acute viral myocarditis (VMC), we infected C57BL/6 mice with Coxsackie virus B3 (CVB3) and examined the effects of the treatment with anti-CD80/CD86 monoclonal antibodies (mAbs) on Th17 cell differentiation in vivo. The effects of anti-CD80/CD86 mAbs on Th17 cell differentiation were further evaluated in vitro. The tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Moreover, CD80 was found to be a marker of the temporal differentiation of Th17 cells ( Fig. 3D), which may provide a mechanistic rationale for the recently reported suppression of Th17 differentiation in response to anti-CD80 treatment in mice (22). These findings therefore suggest that surface expression of CD80 in activated T cells could be mediated by trogocytosis, a CTLA-4-independent mechanism previously described in activated T cells, and shown to alter T-cell function (23,24).…”
Section: Multi-omics Immunophenotyping Approach Identifies Rare Populsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, CD80 was found to be a marker of the temporal differentiation of Th17 cells ( Fig. 3D), which may provide a mechanistic rationale for the recently reported suppression of Th17 differentiation in response to anti-CD80 treatment in mice (22). These findings therefore suggest that surface expression of CD80 in activated T cells could be mediated by trogocytosis, a CTLA-4-independent mechanism previously described in activated T cells, and shown to alter T-cell function (23,24).…”
Section: Multi-omics Immunophenotyping Approach Identifies Rare Populsupporting
confidence: 67%
“…In contrast to CD86, CD80 protein expression could also be detected in Tregs with lower CTLA-4 levels, and displayed broader expression profile in other activated T-cell subsets. In particular the pseudotime analysis in our dataset, identified CD80 as a marker of the temporal differentiation of Th17 cells, which may provide a mechanistic rationale for the recently reported suppression of Th17 differentiation in response to anti-CD80 treatment in mice [35]. Furthermore, we also note a distinct co-expression of CD80 protein and HLA-class II mRNA (HLA-DRA) in a subset of activated Th1 cells, which could indicate recent activation in the context of strong TCR signaling required to induce the differentiation of Th1 cells [36,37].…”
Section: Discussionmentioning
confidence: 53%
“…14,[20][21][22][23] In our experiments we used a standard viral myocarditis mouse model established by CVB3. 4,5 Our results showed that the model had been established successfully as evidenced by decreased cardiac function, increased viral tires and levels of inflammatory cytokines and biomarkers. In addition, the survival rate for the CVB3 infected mice was reduced.…”
Section: Discussionmentioning
confidence: 74%
“…2,3 Viral myocarditis murine models established by Coxsackie virus B3 (CVB3) have been widely studied. 4,5 The pathogenesis of viral myocarditis is complex and some researchers have proposed that excessive innate immune responseinduced inflammation is the major mechanism. 6 Toll-like receptor 4/nuclear factor jB (TLR4/NF-jB) signal pathway is closely related to the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that CD80 (or B7-1) and CD86 (or B7-2) are crucial costimulatory molecules in T cell activation, inducing Th1 and Th2 differentiation, respectively, in host immune responses. Most recently, Huang et al [ 66 ] investigated the role of CD80 and CD86 in Th17 differentiation in AVMC. The authors infected C57BL/6 mice with CVB3 and examined its effects on Th17 differentiation with anti-CD80 and anti-CD86 monoclonal antibodies (McAbs).…”
Section: T Cell-mediated Autoimmunitymentioning
confidence: 99%